2011
DOI: 10.1155/2011/159501
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Keratocyst Looks Can Be Deceptive, Causing Endodontic Misdiagnosis

Abstract: Odontogenic keratocyst (OKC) is the cyst arising from the cell rests of dental lamina. It can occur anywhere in the jaw, but commonly seen in the posterior part of the mandible. Radiographically, most OKCs are unilocular when presented at the periapex and can be mistaken for radicular or lateral periodontal cyst. When the cyst is multilocular and located at the molar ramus area, it may be confused to ameloblastoma. Lots of cases have been reported in the literature where OKC is associated with the nonvital too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 4 publications
(11 reference statements)
1
12
1
6
Order By: Relevance
“…KCOT has been shown to have a bimodal age distribution with first peak in the second and third decades and the second peak in the fifth decade or later. It is said that the lesions in the second peak are more common in maxilla 1 4. But the present case does not follow this conventional norm regarding age and area specificity of the cyst.…”
Section: Discussioncontrasting
confidence: 67%
“…KCOT has been shown to have a bimodal age distribution with first peak in the second and third decades and the second peak in the fifth decade or later. It is said that the lesions in the second peak are more common in maxilla 1 4. But the present case does not follow this conventional norm regarding age and area specificity of the cyst.…”
Section: Discussioncontrasting
confidence: 67%
“…Even though the majority of the reported cases showed predilection to mandibular posterior region [2,4], the present case showed anterior mandiblular predilection which is an unusual location of Keratocystic odontogenic tumor.This was in accordance with other studies which described odontogenic keratocystic lesion in the anterior mandibular segment [7,8].…”
Section: Discussionsupporting
confidence: 94%
“…During our search it became very conspicuous to us that most of the literature is either case reports or case series or miscellaneous studies. This reflects the dearth of information concerning the behavior and management of odontogenic keratocyst.The odontogenic keratocyst (OKC) is regarded as an aggressive lesion due to its characteristic high tendency to recur ,and to invade adjacent tissues [ 15 - 18 ]. In 1967, Toller suggested that the OKC should be classified as a benign tumor rather than a cyst based on its characteristic clinical features [ 19 ].…”
Section: Discussionmentioning
confidence: 99%